The plural form of empirical adequacy in physics (Culturas Científicas, 2025)
In the context of philosophy of physics, it is possible to identify some fundamental problems that, in their formulation, explicitly appeal to the concept of empirical adequacy. Although at first glance it might seem that these problems share the same canonical characterization of this concept, a deeper philosophical analysis shows that the anatomy of the latter depends on assumptions about what is observable or detectable, so it cannot be uniquely defined. In fact, given that what is considered observable o detectable depends on the theory and the philosophical position adopted with respect to it, the very definition of empirical adequacy implies not only that theory but also the position in question. Under these circumstances, the aim of this contribution is to develop a plural characterization of empirical adequacy relative to the spectrum of different philosophical commitments associated with the realism-antirealism debate. Based on this characterization, I shall demonstrate that some fundamental problems addressed within philosophy of physics can only be formulated and make sense through the lens of different particular notions of empirical adequacy, aligned with the spectrum of philosophies that emerge from this debate.
Keywords: Philosophy of physics; Empirical adequacy; Scientific realism; The measurement problem; The macro-object problem; The problem of time